1988
DOI: 10.3354/meps044059
|View full text |Cite
|
Sign up to set email alerts
|

Copper tolerance of the life history stages of the splashpool copepod Tigriopus californicus (Copepoda, Harpacticoida)

Abstract: High concentrations of copper were used to test the hypothesis that a species tolerant to large changes in natural conditions will exhibit tolerance to elevated levels of chemical contamination. The harpacticoid copepod Tignopus californicus was used as a test species because it occurs in supralittoral splashpools and is tolerant to wide-ranging conditions of temperature and salinity. Life history stages were exposed to concentrations of total dssolved copper between I O -~ and I O -~ M in a defined medium wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
4
11
0
Order By: Relevance
“…The molting process may be involved; higher PAH tissue burden was found in newly molted compared to intermolt crabs perhaps as a consequence of increased water uptake and integument permeability at ecdysis or decreased PAH biotransformation rate during the molt process (Mothershead & Hale 1992). Naupliar stages of meiobenthic copepods were consistently the most sensitive in aqueous exposures to heavy metals (Verriopoulus & Moraitou-Apostolopoulou 1982, O'Brien et al 1988, Hutchingson et al 1994) and chlorpyrifos . Higher tolerance of female copepods, as observed with N. lacustris, has been reported for other species of copepods in aqueous and sediment exposures to PCBs (polychlorinated biphenyls) and petroleum hydrocarbons (Dalla Venezia et al 1981, DiPinto et al 1993, Carman & Todaro 1996 and has been speculated to be related to the elimination of hydrophobic contaminants via egg production (Dipinto et al 1993).…”
Section: Effects On Survivalmentioning
confidence: 99%
“…The molting process may be involved; higher PAH tissue burden was found in newly molted compared to intermolt crabs perhaps as a consequence of increased water uptake and integument permeability at ecdysis or decreased PAH biotransformation rate during the molt process (Mothershead & Hale 1992). Naupliar stages of meiobenthic copepods were consistently the most sensitive in aqueous exposures to heavy metals (Verriopoulus & Moraitou-Apostolopoulou 1982, O'Brien et al 1988, Hutchingson et al 1994) and chlorpyrifos . Higher tolerance of female copepods, as observed with N. lacustris, has been reported for other species of copepods in aqueous and sediment exposures to PCBs (polychlorinated biphenyls) and petroleum hydrocarbons (Dalla Venezia et al 1981, DiPinto et al 1993, Carman & Todaro 1996 and has been speculated to be related to the elimination of hydrophobic contaminants via egg production (Dipinto et al 1993).…”
Section: Effects On Survivalmentioning
confidence: 99%
“…In general, however, copper LC 50 should decrease with exposure time. Thus LC 50 after 24 h would be expected to be higher than LC 50 after 48 or 96 h. What this suggests is a higher tolerance for one species when the 96-h LC 50 value is equal to or greater than the 48 or 24 h LC 50 value for a second species [28]. Following Cu exposure, no significant differences between the endpoints of 'moult reduction' and mortality were found, despite literature reports of other crustacean species showing an increase in moult frequency after Cu exposure [38].…”
Section: Discussionmentioning
confidence: 89%
“…For example, in experiments with meiobenthic and splashpool copepods exposed to metals, pesticides and polychlorinated biphenyls, it was reported that juveniles (nauplii) were two to four times more sensitive than adults [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Toxicologists have long been aware of the contrasting effects that toxins have on individuals of different ages/life stages. [25][26][27][28][29] Most of their work has focused on specifics regarding metabolic and general physiological reactions of individuals of different ages or stages. In contrast, for their part, many ecologists that model disturbance regimes often blatantly ignore subtle differences in how different individuals within a population are affected.…”
Section: Different Strokes: An Enigmatic Split In Perspectivementioning
confidence: 99%